Factors Contributing to Additional Disabilities in Leprosy Patients during Treatment in Thailand - Bamphenyu, Saowanee; Tessana, Nongluck; Thanyakittikul, Podjana; Patsadon, Supannee (Journal of Health Science of Thailand, 2018)
Disability in leprosy patients can occur before, during and after complete treatment. Preven-tion of disability (POD) during treatment is aimed at preventing further additional disability whichmay occur during such period. In 1990, National Leprosy Programme (NLEP) by Leprosy Divisionundertook the “Evaluation of Leprosy Elimination Programme” and found that less than 50 percentof health units could provide qualified nerve function assessment (NFA), and 10 percent of leprosypatients suffered additional disabilities during treatment. The objectives of this health system re-search were to identify factors contributing to additional disability developed during treatment inleprosy patients, in order to recommend on coverage and quality of POD service in Thailand. Theresearch methodology was cross-sectional descriptive study. The quantitative research part wasconducted by distributing questionnaires to find the coverage and quality of POD services in healthunits of ministry of public health (MOPH). The qualitative research part was in-depth interviews ofhospital directors, doctors, health workers and leprosy patients, observing POD services system.Documentary review covered OPD cards, leprosy patient cards, POD record forms, health educa-tion checklist forms, leprosy manual, leprosy clinical practice guideline (CPG) and annual report in12 hospitals sampled out of 12 Disease Prevention and Control offices. The results revealed that212 hospitals (29.7%) of all MOPH hospitals in Thailand provided POD services, with only 178hospitals (24.9%) could provide qualified POD services. When it was compared to that in 1998, adecline was observed. Factors contributing to the decreasing coverage and quality of POD serviceson the provider’s side were policy declaration, human resource administration, workload, servicesystem, knowledge, attitude, complexity and monitoring, priority and complexity of POD activities.Factors on patient side were unaware of one’s right to receive POD services, receivingincomprehensive treatment and care of complications emerging during MDT treatment and lack ofcounselling. Most patients were optimistic with respect to providers and POD activities. It isrecommended that improvements are to be made in terms of policy, strategies and activities torevitalize leprosy control system. Focus should be made on human resource development, referralsystem, setting up hotline services system and adequate leprosy experts are needed.